Land relations monitoring in Ukraine: status and prospects for development - Butenko, E.; Kononyuk, A. (Land Management, Cadastre and Land Monitoring, 2020)
The article analyzes the prospects of development of land relations monitoring, principles of its functioning and tendencies on the basis of consciously selected indicators and scientifically sound methods. Reliable monitoring data is difficult to obtain in situations existing in different areas characterized by large areas and significant spatial and temporal characteristics. Proper use of these tools allows the information collected through monitoring activities to serve as a basis for assessing whether resource conditions are changing or not and whether these changes are desirable. One of the main problems is considered - the closed access to the information on land relations, which allows against the national and local public interests, officials and related selfish intentions to use the land for their own interests. And this closure raises many problems. Emphasized on the creation of an open, constantly updated database on land relations, which will become an integrated information network for monitoring entities, will provide a new level of transparency, local decision-making awareness. This will provide a new level of transparency in land relations and will focus on improving land use and creating the conditions for effective governance. Keywords: Land monitoring, land relations, remote sensing, automation, database.